2011
DOI: 10.1111/j.1442-9071.2011.02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported diabetes and diabetic retinopathy in indigenous Australians: the National Indigenous Eye Health Survey

Abstract: The prevalence of self-reported diabetes in indigenous Australians is more than eight times higher than that in non-indigenous Australians. The prevalence of diabetic retinopathy in people with diabetes is similar to that of non-indigenous Australians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 23 publications
7
31
0
Order By: Relevance
“…Our findings are consistent with previous epidemiological evidence reporting a significantly higher prevalence of diabetes in Indigenous Australians compared to non-Indigenous Australians, and with an earlier age of onset of the disease [810]. We found that the prevalence of self-reported diabetes (43.77%) was higher than that identified in the NIEHS in 2008 (37.3%) [10].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are consistent with previous epidemiological evidence reporting a significantly higher prevalence of diabetes in Indigenous Australians compared to non-Indigenous Australians, and with an earlier age of onset of the disease [810]. We found that the prevalence of self-reported diabetes (43.77%) was higher than that identified in the NIEHS in 2008 (37.3%) [10].…”
Section: Discussionsupporting
confidence: 92%
“…In Australia alone, 1.5 million adults have diabetes and the number is predicted to increase to 2.9 million by the year 2025 [6, 7]. The prevalence of diabetes is much higher in Indigenous Australians and the onset of diabetes occurs at a significantly younger age than in non-Indigenous Australians [810]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of various manifestations of diabetic retinopathy in Indigenous people varies considerably but overall is similar to that of non-Indigenous people [7,15]. Worldwide the prevalence of any diabetic retinopathy is approximately 35%, while among Indigenous people it ranges from 17% in Canadian First Nation and Metis to approximately 50% in New Zealand Maori [7].…”
Section: Diabetic Complications In Indigenous People: Nephropathy and Rmentioning
confidence: 99%